A phytochemical study of Morinda roioc L. (Family Rubiaceae) and alkaloids in aged potatoes, Solanum tuberosum L. (Family Solanaceae) - Park, Young Han
Part 1: Twelve anthraquinones, damnacanthal, nordamnacanthal, copareolatin-1 (or 5), 6-dimethyl ether, 2-formyl-3-hydroxyanthraquinone, morindone, soranjidiol, rubiadin-1-methyl ether, lucidin, tectoquinone, copareolatin-6-methyl ether, morindone-5-methyl ether, and soranjidiol-1-methyl ether, and methyl palmitate were isolated from 10% aqueous methanol and sodium carbonate soluble fractions of roots of Morinda roioc. 2-Formyl-3-hydroxyanthraquinone, morindone-5-methyl ether, and soranjidiol-1-methyl ether have been reported for the first time as natural products. Damnacanthal, nordamnacanthal, 2-formyl-3-hydroxyanthraquinone, and lucidin were found to have antibacterial activity against Bacillus subtilis, Staphylococcus aureus, and Mycobacterium smegmatis.